Variability in conceptualizations and measurement of genetic literacy - Brianne M. Daly; Kimberly A. Kaphingst (Elsevier, 2023)
Objective: To examine definitions and measures for genetic literacy in the published literature, and the associations between commonly utilized measures. Methods: We completed a systematic review searching eight databases for empirical articles containing quantitative measures of genetic literacy. Articles were assessed for study properties, definitions, and measure characteristics. An online survey was then completed by 531 U.S. adults to examine correlations between frequently used genetic literacy measures. Results: 92 articles met inclusion criteria for the systematic review. Articles rarely defined genetic literacy, and existing definitions showed inconsistencies in the knowledge and cognitive domains that comprise genetic literacy. Definitions frequently included objective conceptual knowledge, comprehension, and applied knowledge, however most measures only assessed objective or subjective knowledge. Genetic literacy measures were infrequently assessed for psychometric properties and the content domains assessed by measures varied considerably. Correlation analyses showed weak to moderate relationships between genetic literacy measures. Conclusion: A comprehensive and consistent definition of genetic literacy and its cognitive and conceptual domains should be implemented to inform the development of concordant measurement tools and improve research and clinical care in genetics. Innovation: We examine and compare definitions and measures of genetic literacy, suggest a more comprehensive definition, and recommendations for research development.